Importing first aid for physical education professionals: an integrative review (Research, Society and Development, 2022)
Introduction: First aid can be defined as the immediate care that must be provided quickly to people in potentially fatal physical conditions. During the exercise of their profession, the professional may face different situations where they need to intervene properly. Thus, the present study aimed to portray what the evidence shows about the importance of first aid for Physical Education professionals. Methodology: This was an integrative review in order to gather and synthesize the results. Results: With the research it was evidenced that most of the working professionals still have little or no knowledge about first aid and the importance of a greater preparation of educators to proceed in sometimes untimely circumstances. Emphasizing the need to update the National Curriculum Guidelines (DCN) of the Physical Education course, as well as the need for practical applicability of first aid concepts by these professionals.